2004
DOI: 10.1002/sim.1539
|View full text |Cite
|
Sign up to set email alerts
|

Estimating life expectancy and related probabilities in screen‐detected breast cancer patients with restricted follow‐up information

Abstract: Issues such as life expectancy after diagnosis, the number of life years gained by early diagnosis through screening, the probability of dying from breast cancer or of dying from other causes during the lead time period or thereafter can be derived from information on complete survival after diagnosis. A method is presented to estimate complete survival and relevant outcomes after diagnosis of screen-detected cancer when the follow-up period is substantially shorter than the maximum follow-up possible. Surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
2
1
4
Order By: Relevance
“…For example, as compared with otherwise healthy non-diseased individuals, we demonstrated that patients with heart failure had life expectancies in keeping with many advanced malignant diseases. [38][39][40][41] However, sex-specific differences in average life-spans that are known to exist among otherwise healthy populations were observed to have been only modest or negligible in our study. Specifically, as abstracted from life-table data, the average life-expectancies of healthy men and women ages 50-60 years are 24.7 and 32.7 years respectively.…”
Section: Discussioncontrasting
confidence: 78%
“…For example, as compared with otherwise healthy non-diseased individuals, we demonstrated that patients with heart failure had life expectancies in keeping with many advanced malignant diseases. [38][39][40][41] However, sex-specific differences in average life-spans that are known to exist among otherwise healthy populations were observed to have been only modest or negligible in our study. Specifically, as abstracted from life-table data, the average life-expectancies of healthy men and women ages 50-60 years are 24.7 and 32.7 years respectively.…”
Section: Discussioncontrasting
confidence: 78%
“…Extrapolation of survival functions is also carried out within cost‐effectiveness studies, often by the use of parametric distributions . Because of the problem with extrapolation, restricted mean survival, the area beneath the survival curve up to a certain point in time, is sometimes estimated .…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios mencionan que el diagnóstico precoz del cáncer de mama puede reducir el riesgo de muerte temprana del 79% al 56%, a los 50 años; mientras que a los 79 años, la relación es de 23 a 13% (8). Además, los autores confirman que la detección primaria de masas o abultamientos en las mamas al momento del autoexamen de mama (AEM), aumenta la posibilidad de reducir el tamaño del tumor en los primeros estadios con quimioterapia, radioterapia o cirugía como primera medida para conservar la mama y evitar el riesgo de metástasis por cáncer invasivo en etapa temprana (9,10).…”
Section: Discussionunclassified